Highlights of practical applications of agents, multi-agent systems, and complexity : The PAAMS collection : International Workshops of PAAMS 2018, Toledo, Spain, June 20-22, 2018, Proceedings /: The PAAMS collection : International Workshops of PAAMS 2018, Toledo, Spain, June 20-22, 2018, Proceedings. (2018) - Unknown
No abstract available